Follicle‐stimulating hormone receptor expression in soft tissue sarcomas. Issue 1 (9th May 2013) - Renner, Marcus; Goeppert, Benjamin; Siraj, Muhammad Ahsan; Radu, Aurelian; Penzel, Roland; Wardelmann, Eva; Lehner, Burkhard; Ulrich, Alexis; Stenzinger, Albrecht; Warth, Arne; Vogel, Monika Nadja; Weichert, Wilko; et al.
<x xml:space="preserve">Abstract</x> Aims In adult humans, the follicle‐stimulating hormone receptor (FSHR) is expressed only in the granulosa cells of the ovary and the Sertoli cells of the testis. Recently, it has been shown that FSHR is expressed selectively on the surface of blood vessels in a wide range of tumours. So far, the expression of FSHR in mesenchymal tumours has not been studied. Methods and results We performed a semiquantitative evaluation of FSHR protein expression in a large cohort of soft tissue sarcomas (STS; n = 335), including 11 subtypes. FSHR‐positive vessels were detected in all sarcoma subtypes analysed. Among liposarcomas, significantly more cases of dedifferentiated liposarcomas (28 of 44) showed FSHR expression compared to well‐differentiated liposarcomas (WDLS; four of 21; P < 0.001). Vessels in lipomas (n = 9) and non‐neoplastic fat were FSHR‐negative. FSHR expression was also detected in tumour cells of all sarcoma subtypes examined, with the lowest incidence in WDLS (three of 21; 14.3%) and the highest frequency in undifferentiated high‐grade pleomorphic sarcomas (41 of 60; 68.3%). Conclusions These data supplement the previously reported results of FSHR expression in endothelial cells of various cancer types and form a solid basis for further studies of FSHR in mesenchymal neoplasms.